Employee Performance Measurement at PT. Cahaya Mekanindo Perkasa Using the Human Resources Scorecard Method - Ilyas Habibi; Aulia Fashanah Hadining (Sainteks: Jurnal Sain dan Teknik, 2023)
Measuring employee performance is a step that companies can take as an evaluation in maintaining company productivity. This also applies to PT. Cahaya Mekanindo Perkasa because at the time the research was carried out, this company did not yet have a performance measurement system, which would result in a decrease in company productivity and worse, losses for the company. The purpose of this research is to provide a proposal for a performance measurement system using methodsHuman Resources Scorecard and as a source of input for employee performance evaluation. This quantitative and descriptive type of research was conducted with a sample size of 16 employees. The results of this research show performance measurement using the methodHuman Resources Scorecard, that isHuman Resources Competency 306 means satisfactory, High Performance Work System 206 means satisfactory, Human Resources Deliverable 245 means satisfactory, and Human Resources Efficiency 307 means satisfactory.